911Which patients are most likely to benefit from the wearable cardioverter-defibrillator? Findings from the Swiss WCD registry. (18th June 2020) - Kovacs, B; Reek, S; Linka, A; Ammann, P; Mueller, A S; Reichlin, T; Haegeli, L; Steffel, J; Saguner, A M; Burri, H; Duru, F
Abstract: OnBehalf: Swiss WCD Registry Introduction: The wearable cardioverter-defibrillator (WCD) has established itself as a temporary protection from sudden arrhythmogenic death in selected patients at risk. However, it is still of debate which patients and for what duration benefit from its use. Therefore, appropriate patient selection is key. Purpose: This study reports the results of the Swiss WCD registry with an emphasis on implantable cardioverter-defibrillator (ICD) implantation rate and ICD therapies. Methods: We retrospectively reviewed the indications, baseline characteristics and administered therapies in patients prescribed a WCD at 12 participating centers rom 2014 until 2018 in Switzerland. Further data on medical therapy, WCD therapy adherence, and ICD implantation rates were collected. Results: 456 patients were included in our study comprising of 66% of all Swiss patients prescribed a WCD in the examined time period. The mean age was 57 ±14 years, 18% were female and the mean ejection fraction (EF) was 32% ± 13. Indications for WCD use and appropriate shock rate are shown in the figure. Patients wore the WCD over a median of 58 days (range 1-455) with a median daily average wear-time of 22.6 hours (range 0.6-23.8). 17 appropriate therapies were administered by the WCD to a total of 12 patients leading to a therapy rate of 2.6% over a median wear-time of 16 days (range 2-79) and to a therapy rate of 3.9% in patients with ischemic cardiomyopathy (ICM) with an EF ≤35%. ICM with an EF ≤35% and bridging to ICD-implantation or heart transplantation as indication for WCD prescription were significantly associated with an appropriate therapy (p = 0.046 and 0.003, respectively). One patient with non-ischemic cardiomyopathy (NICM) received an appropriate therapy (0.8%). The mean EF in patients receiving an appropriate therapy by the WCD was also significantly lower (p = 0.04). No patient with wearing the WCD for congenital/inherited heart disease or risk stratification with an EF >35% had a therapy administered by the WCD. There were no inappropriate therapies during the investigated time period. After cessation of WCD use EF improved to 38% ±13; ultimately, 212 patients (46%) were implanted with an ICD. During a follow-up of 476 days (range 7-2347) 22 (9.8%) patients received an appropriate therapy by their ICD. Four of the 22 had prior appropriate therapy by the WCD. Conclusions: ICM with severely reduced EF was the most common indication for WCD use leading to a high rate of appropriate therapy by the WCD. This, however, did not translate in a higher rate of appropriate ICD-therapies during follow-up in this subpopulation possibly due to significant improvements in their ejection fractions. Patients with NICM or congenital/inherited heart disease seldom had an appropriate therapy by the WCD.